Technical compliance to standard guidelines for lumbar puncture and myelography: survey of academic neuroradiology attendings and fellows - Zhang, Yi C; Chandler, Alexander J; Kagetsu, Nolan J (Academic radiology, 2014)
To assess technical compliance among neuroradiology attendings and fellows to standard guidelines for lumbar puncture and myelography to minimize procedural complications such as iatrogenic meningitis and spinal headache. We surveyed academic neuroradiology attendings and fellows in the e-mail directory of the Association of Program Directors in Radiology. We queried use of face masks, use of noncutting needles, and dural puncture practices. All data were collected anonymously. A total of 110 survey responses were received: 75 from neuroradiology attendings and 34 from fellows, which represents a 14% response rate from a total of 239 fellows. Forty-seven out of 101 (47%) neuroradiologists do not always wear a face mask during myelograms, and 50 out of 105(48%) neuroradiologists do not always wear a face mask during lumbar punctures, placing patients at risk for iatrogenic meningitis. Ninety-six out of 106 neuroradiologists (91%) use the Quincke cutting needle by default, compared to only 17 out of 109 neuroradiologists (16%) who have ever used noncutting needles proven to reduce spinal headache. Duration of postprocedure bed rest does not influence incidence of spinal headache and may subject patients to unnecessary monitoring. Only 15 out of 109 (14%) neuroradiologists in our study do not prescribe bed rest. There was no statistically significant difference in practice between attendings and fellows. Iatrogenic meningitis and spinal headache are preventable complications of dural puncture that neuroradiologists can minimize by conforming to procedural guidelines. Wearing face masks and using noncutting spinal needles will reduce patient morbidity and lower hospitalization costs associated with procedural complications.